Qualitative assessment of the level of natural content of heavy metal compounds natural content level in the basins of the Malka, Urukh, Cherek, and Chegem rivers - Sergey L. Alita; Fatimat A. Atabiyeva; Elena A. Cherednik; Asiyat S. Otarova (Водное хозяйство России: проблемы, технологии, управление)
To date, considerable experience has been accumulated in assessing and standardizing the quality of natural waters, however, the role of regional factors in practical standardization in most cases is ignored. Due to the lack of recommendations for establishing permissible loads on a water body, taking into account its natural characteristics, the effectiveness of water protection measures is reduced. Determination of the concentrations of pollutants using maximum permissible concentrations without taking into account the hydrological and hydro/chemical characteristics of water bodies does not ensure the environmental safety of the water body. The regulation of the water quality of water bodies must necessarily reflect the regional features of the formation of the chemical composition of natural water in a particular territory, since the soil and geochemical features of the catchment area of the basin reflect natural background concentrations.